Diversidade e estrutura de comunidades microbianas associadas à rizosfera de Rhyzophora mangle do manguezal do Rio Pacoti, zona leste da costa cearense - Colares, Geórgia Barguil (2010)
Mangroves are coastal ecosystems which occur in tropical and subtropical regions, subjected to tidal action. These ecosystems are very important for species reproduction and act as shoreline protectors. Mangroves are usually highly populated areas and are exposed to various human impacts, such as the discharge of untreated sewage, deforestation and river silting. These impacts affect populations of animals, plants and microorganisms that inhabit these areas, causing a loss of diversity. The mangrove soil microorganisms represent a considerable portion of the activities of nutrient cycling and decomposition of waste with a fundamental importance for the ecosystem balance. However, studies focusing on the diversity and structure of microorganism communities in mangroves soils are still limited by cultivation techniques. With the advance of the molecular biology techniques, using the gene encoding the 16S subunit of the ribosomal RNA, the study of microbial communities that would not be accessed by traditional methods of cultivation was enabled. Thus, this study aims to investigate the structure and diversity of soil microbial communities from the rhizosphere of Rhizophora mangle from the Pacoti River, located in the metropolitan region of Fortaleza, using Denaturing Gradient Gel Electrophoresis (DGGE), obtaining diversity profiles and characterizing the mangrove microbial communities and to compare it to the data obtained from the environmental variables and soil characteristics. Results showed that the mangrove soils microbial communities are similar in number of OTUs, but differ in composition. The physical and chemical variables and soil characteristics are responsible for the differences in the microbial communities‟ composition and structure, although the rhizosphere effect determines the occurrence of various OTUs in common among the sampling sites. The communities‟ diversity analysis showed that they are in balance due to the fact that there is no dominance of OTUs and the communities present spatial and temporal similarities. In conclusion, the Rhizophora mangle rhizosphere soils of the Pacoti River mangrove harbor diverse and stable microbial communities that differ in structure and in composition